2003
DOI: 10.1007/bf03218362
|View full text |Cite
|
Sign up to set email alerts
|

EVA/clay nanocomposite by solution blending: Effect of aluminosilicate layers on mechanical and thermal properties

Abstract: Ethylene vinyl acetate (EVA)/clay nanocomposites were synthesized by blending a solution of ethylene vinyl acetate copolymer containing 12% vinyl acetate abbreviated as EVA-12 in toluene and dispersion of dodecyl ammonium ion intercalated montmorillonite (12Me-MMT) in N,N-dimethyl acetamide (DMAc). X-ray patterns of sodium montmorillonite (Na + -MMT) and 12Me-MMT exhibited d 001 peak at 2θ = 7.4 o and 2θ = 5.6 o respectively; that is, the interlayer spacing of MMT increased by about 0.39 nm due to intercalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 27 publications
(23 reference statements)
3
23
0
Order By: Relevance
“…This is because of the fact that, beyond 4-6 wt.-% of clay content, aluminosilicate layers probably start to aggregate in the EVA matrix as observed in our earlier works on EVA. [17][18][19][20] An exclusive TEM photograph of EVA/12Me-MMT nanocomposite containing 2 wt.-% filler was produced with the help of high resolution microscope (CM 12, Philips) with an acceleration voltage of 120 kV, where it is observed that the aluminosilicate layers are dispersed homogeneously and randomly on nano-level in EVA matrix shown in Figure 4(a). Additionally, another one TEM photograph of EVA/12Me-MMT nanocomposite with 8 wt.-% 12Me-MMT is displayed in Figure 4(b), where the aggregated aluminosilicate layers marked by dark densed portion are noticed very distinctly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because of the fact that, beyond 4-6 wt.-% of clay content, aluminosilicate layers probably start to aggregate in the EVA matrix as observed in our earlier works on EVA. [17][18][19][20] An exclusive TEM photograph of EVA/12Me-MMT nanocomposite containing 2 wt.-% filler was produced with the help of high resolution microscope (CM 12, Philips) with an acceleration voltage of 120 kV, where it is observed that the aluminosilicate layers are dispersed homogeneously and randomly on nano-level in EVA matrix shown in Figure 4(a). Additionally, another one TEM photograph of EVA/12Me-MMT nanocomposite with 8 wt.-% 12Me-MMT is displayed in Figure 4(b), where the aggregated aluminosilicate layers marked by dark densed portion are noticed very distinctly.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] Square or rectangular shape of these nanocomposites were cut and weighed. The weighed (W i ) samples were immersed in xylene and allowed to swell at room temperature (28.5 8C).…”
Section: Swelling Technique and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…( Alexandre & Dubois, 2000;Awad et al, 2009;Braganca et al, 2007;Kawasumi et al, 1997;Kaynak et al, 2009;Maiti et al, 2002;Pramanik et al, 2003;Ray et al, 2003). The stable grafting of the polymer chains to the inorganic clay substrate may have also contributed to the increased tensile modulus of the clay-filled poly(norbornene) films.…”
Section: Figure 5 Loss and Storage Moduli Of (A) Free Poly(norbornenmentioning
confidence: 99%
“…1,2 When inorganic nanoparticles are incorporated in the polymer solutions, their flow properties might be changed differently from those of micronsized particle filled ones due to unusually large specific surface area. The adsorption phenomena of polymers on solid nanoparticles are known to influence strongly the microstructure of polymer/particle systems.…”
Section: Introductionmentioning
confidence: 99%